Answer:
One fourth
Step-by-step explanation:

Step-by-step explanation:
(2b-3)/(b-2)(b+2) = 3b(b-2)/(b+2)(b-2)
2b²+4b-3b-6/b²-4=3b²-6b/b²-4
2b²+b- 6= 3b²-6b
move square to square unknown to unknown
-b²+7b-6/b²-4
i also dk this is true or false
To determine the cost of each item, we need to set up equations. From the problem statement, we have three unknowns so we need three equations. We set up equations as follows:
let x cost of small pizzas
y cost of soda
z cost of salad
two small pizzas, a liter of soda, and a salad cost $14
2x + y + z = 14
one small pizza, a liter of soda, and three salads cost $15
x + y + 3z = 15
three small pizzas, a liter of soda, and two salads cost $22
3x + y + 2z = 22
Solving for x, y and z, we will have:
x = $ 5
y = $ 1
z = $ 3
Answer:
-259
Step-by-step explanation:
brainliest
At least about 20 points it can depend on the class but not really.